Voice expression in Middle Armenian verbs with conversion - Khachatryan, Alvard (Bulletin of Yerevan University B: Philology, 2022)
The change of conjugating vowels is one of the peculiar manifestations of verbal conversion. If, during morphological conversion, a word from one part of speech passes into another, then when changing conjugating vowels, only the construction of the verb, the type of conjugation changes, however, in some cases, the voice of the verb may also change, such as էրել (active) -էրիլ (neutral), կտրել (active)-կտրիլ (neutral), շիւարել (neutral)–շիւարիլ (neutral), etc. To study the process of changing literary languages ​​- the transition of Old Armenian to Middle Armenian, it is important to identify the regularities of verbal conversions, in which voice changes are possible. This article examines the verbs of the Middle Armenian literary language in comparison with the Old Armenian, and shows the main vectors of the development of verb forms both in terms of expression and in terms of content. Most often, the change of glowing vowels does not exceed the verb and change only the composition of the verb, suffixes are added to the root, for example, դժարեմ/դժարանամ, տափկիմ/տափականամ, ժանկիմ-ժանգանամ, աժեմ/աժենամ, վառիմ-վառենամ etc. A special suffix ու/ւ/վ has already appeared in Middle Armenian to express passive voice, for example, լցվել-լցւիլ/լցուիլ, բացուել/բացւել-բացուիլ.